Inovação na cadeia do agronegócio: proposta e aplicação de ferramenta para analise do nível de maturidade - Baptista, Fabio Solano (2024)
Brazil has one of the largest territorial extensions on the planet, with a significant portion dedicated to arable land, placing the country among the world's largest agribusiness producers. This sector faces challenges from increasing demand for quality products, growing environmental concerns, and economic pressures. This scenario requires constant innovations to maintain productivity and competitiveness on an international scale. Therefore, given the importance of innovation in the agribusiness sector, this study aims to analyze the maturity level of innovation management in the supply chain of an agro-industrial cooperative in Brazil. To achieve this objective, a systematic literature review was conducted using the Methodi Ordinatio 2.0 methodology, and an empirical study was carried out through the application of a data collection instrument. This approach aimed to highlight strategic gaps for innovation within the studied cooperative. The field research reveals distinct maturity levels of innovation across various business units in the supply chain, identifying clusters that organize areas with higher and lower degrees of innovation. The analysis of the cooperative under study is based on the macroprocesses of production activities, demonstrating the specific maturity levels of these processes. The results provide a basis for developing strategies that can contribute to the implementation of innovative solutions, not only in the studied cooperative but also in other cooperatives within the same sector.